2007
DOI: 10.1002/ijc.22894
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD25hi regulatory T‐cell frequency correlates with persistence of human papillomavirus type 16 and T helper cell responses in patients with cervical intraepithelial neoplasia

Abstract: CD4 1 CD25 hi CTLA4 1 FoxP3 1 regulatory T cells (Treg) have been shown to maintain immune tolerance against self antigens and increased circulating frequencies have been reported in various types of cancers. Circulating invariant natural killer T-cells (iNKT) are reduced in cancer patients and low iNKT frequency is related to poor prognosis. It is not yet clear whether high Treg numbers and low iNKT cell numbers pose an increased risk for the progression of premalignant lesions or whether Treg and iNKT cell n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
89
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(100 citation statements)
references
References 44 publications
10
89
0
1
Order By: Relevance
“…18,29 A direct relationship between the HPV infection and the onset of an immune suppressive environment has been suggested by a prospective study of HPV16-related lesions, in which regulatory T cell frequencies were significantly increased in women who had persistent HPV16 infection and HPV16-specific interleukin-2 producing T-helper cells. 19 Furthermore, it has also been observed that, in patients with HPV6-and HPV11- …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,29 A direct relationship between the HPV infection and the onset of an immune suppressive environment has been suggested by a prospective study of HPV16-related lesions, in which regulatory T cell frequencies were significantly increased in women who had persistent HPV16 infection and HPV16-specific interleukin-2 producing T-helper cells. 19 Furthermore, it has also been observed that, in patients with HPV6-and HPV11- …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, high levels of CXCL12 expression result in reduced infiltration of the tumor by tumor antigen-specific T cells 17 and the suppression of antitumor immune responses via various mechanisms including the intratumoral accumulation of FoxP3 ϩ suppressor T cells. 18,19 We hypothesized that secretion of CXCL12 by cervical tumors is correlated with progression of the tumor and loss of immune control. To explore this hypothesis we first examined whether clinicopathological progression of cervical cancer is associated with an increase in CXCL12 expression and a concomitant reduction in immune cell infiltration into the tumor as the tumor progresses from a preinvasive to an invasive state.…”
mentioning
confidence: 99%
“…One research group has made extensive use of their study population to characterize several aspects of immune response as measured in PBMCs (de Gruijl, Bontkes et al 1998;Bontkes, de Gruijl et al 1999;de Gruijl, Bontkes et al 1999;Bontkes, de Gruijl et al 2000;Molling, de Gruijl et al 2007). However, few studies have been so thorough.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…al. (Molling, de Gruijl et al 2007) evaluated cultured PBMCs again stimulated with 14 different 20mer HPV16 E7 peptides or with PHA and measured both IL-2 levels and CTL activity. Importantly, they also measured invariant natural killer T-cells (iNKT) and FoxP3+ regulatory T cells (Tregs) levels by flow cytometry (FACSCalibur).…”
Section: Introductionmentioning
confidence: 99%
“…41 Moreover, cervical lesions in patients with HPV161 or HPV181 tumors are highly infiltrated with CD4 1 FoxP3 1 T cells whereas they are mostly absent in the normal cervix. 42 This suggests that amongst the population of tumor-infiltrating lymphocytes, there is a significant population that can suppress antitumor immune responses within the tumor itself if the endogenous or vaccine-induced CTL response to HPV antigens is not great enough.…”
Section: Role Of Regulatory T Cellsmentioning
confidence: 99%